Long-term positive effect of an educational antimicrobial stewardship program implemented in an Internal Medicine Department: a prospective analysis and a point prevalence survey on long-term effect. (19th May 2021) - Cona, Andrea; Iannotti, Nathalie; Gazzola, Lidia; Aldieri, Chiara; Viganò, Ottavia; Bini, Teresa; Marchetti, Giulia; Monforte, Antonella d'Arminio
Abstract : The study aims to evaluate antimicrobial consumption and appropriateness one year after the implementation of an antimicrobial stewardship (AMS) program in an Internal Medicine Department in Milan. AMS program structured in two phases: "AMS phase", 5 months AMS-program based on an "audit-and-feedback model"; the "follow-up phase", 5 months long point prevalence survey conducted one year later. Outcomes of the study: antimicrobial consumption and appropriateness of antimicrobial therapy. Secondary outcomes: in-hospital mortality and length of stay (LOS). During the "AMS phase", we obtained a mean decrease of −11.4% of total antibiotic consumption as compared to the previous year (67.9 defined daily dose (DDD)/100 bed-days (bd) vs. 79.4 DDD/100bd, p  = 0.07). Antibiotic consumption remained stable during "follow-up phase" (66.3 DDD/100bd, p  = 0.9). Rate of appropriateness during the project increased from 48% to 85% ( p  < 0.01). No difference in in-hospital mortality and in LOS were observed. The study documents a positive long-term effect of AMS program on consumption and appropriate use of antibiotics.